Identification of novel Theileria genotypes from Grant's gazelle. Issue 2 (August 2015) - Hooge, Janis; Howe, Laryssa; Ezenwa, Vanessa O.
Highlights One hundred percent of 65 Grant's gazelle blood samples were PCR-positive for Thelieria/Babesia. Sequencing of PCR amplicons revealed widespread Theileria co-infections. Isolates from singly infected animals fell into two Theileria subgroups. One of these subgroups clustered with Theileria ovis isolates from livestock. The gazelle Theileria lineages represent novel genotypes.